Speech peculiarities of the character’s impulsive type in English short stories - Klokova, Anna G. (Journal of the Belarusian State University. Philology, 2019)
The article deals with a relevant present time aspect of the correlation between speech features and psychological reasons for different specific ways of speech representation. Lingvopsychological analysis of the character’s and the author’s speech which is based on the personality typology of three characterological types is given. The article describes an impulsive character that is embodied through the author’s speech first and then through his own speech. The comparative analysis helps reveal speech features (discursive markers) defining speech behavior of the impulsive type in English short stories.